SHARP – VI. Evidence for CO (1–0) molecular gas extended on kpc-scales in AGN star-forming galaxies at high redshift. Issue 2 (16th May 2020) - Spingola, C; McKean, J P; Vegetti, S; Powell, D; Auger, M W; Koopmans, L V E; Fassnacht, C D; Lagattuta, D J; Rizzo, F; Stacey, H R; Sweijen, F
ABSTRACT: We present a study of the stellar host galaxy, CO (1–0) molecular gas distribution and AGN emission on 50–500 pc-scales of the gravitationally lensed dust-obscured AGN MG J0751+2716 and JVAS B1938+666 at redshifts 3.200 and 2.059, respectively. By correcting for the lensing distortion using a grid-based lens modelling technique, we spatially locate the different emitting regions in the source plane for the first time. Both AGN host galaxies have 300–500 pc-scale size and surface brightness consistent with a bulge/pseudo-bulge, and 2 kpc-scale AGN radio jets that are embedded in extended molecular gas reservoirs that are 5–20 kpc in size. The CO (1–0) velocity fields show structures possibly associated with discs (elongated velocity gradients) and interacting objects (off-axis velocity components). There is evidence for a decrement in the CO (1–0) surface brightness at the location of the host galaxy, which may indicate radiative feedback from the AGN, or offset star formation. We find CO–H2 conversion factors of around αCO = 1.5 ± 0.5 (K km s −1 pc 2 ) −1, molecular gas masses of >3 × 10 10 M⊙, dynamical masses of ∼10 11 M⊙, and gas fractions of around 60 per cent. The intrinsic CO line luminosities are comparable to those of unobscured AGN and dusty star-forming galaxies at similar redshifts, but the infrared luminosities are lower, suggesting that the targets are less efficient at forming stars. Therefore, they may belong to the AGN feedback phase predicted by galaxy formation models, because they are not efficiently forming stars considering their large amount of molecular gas.